Impact of Iron Deficiency Anemia on the Severity of Bronchiolitis in Pediatric Patients - Rizwan Ali; Farhana Zafar; Rida Mukhtar (Pakistan Journal of Health Sciences, 2026)
Bronchiolitis is an acute inflammatory respiratory illness involving the lower respiratory tract occurring in the first 2 years of life. Objectives: To determine the impact and outcomes of the severity of iron deficiency anemia (IDA) in patients with acute bronchiolitis (AB). Methods: This analytical, cross-sectional study was conducted in the Department of Pediatric Medicine, Ziauddin University Hospital, Karachi, Pakistan, from April 2025 to September 2025. A total of 126 children aged 2–23 months with AB were enrolled through non-probability consecutive sampling. Bronchiolitis severity was classified by the Wang score. Data were analyzed using SPSS version 26.0, with p